Performances of two commercially available Newcastle disease vaccines in Bangladesh: A case-control study - Kashem, M A; Hashem, M A; Kabir, M H B; Uddin, M I; Hasan, B (Bangladesh Journal of Microbiology, 2012)
The study was conducted to test the performances of two commercially available live vaccines named BCRDV1(VG/GA strain) and BCRDV2 (F-strain). A total of 90 day-old broiler birds were divided into three different groups and the serum samples were collected at day 1, 7, 14, 21, 28 and 35; mean±SD of Haemgglutination Inhibition (HI) titres (log2) were found as 8±0.00, 7.2±0.89, 6.1±0.9, 7.1±0.75, 5.7±0.72, 4.1±0.68 and 8±0.00, 6.0±0.76, 4.8±0.81, 5.8±0.83, 4.9±0.86, 3.8±0.77 in group I and group II respectively, which was significant (P< 0.01). In control (group III) the mean±SD was found to be 8±0.00, 5.8±0.87, 4.9±0.69, 4.1±0.48, 3.0±0.56 and <2±0 respectively. The titres of control group infer that the maternal antibody usually had a tendency to decline and may pose a risk of infection. In protection test, 100% mortality were found in control group (III) but in group I and group II the mortality of birds were 6.67% and 10%, respectively. The analysis of HI titres with the target to determine the performance of two vaccines revealed that BCRDV1 vaccinated groups was able to maintain significantly higher HI titres than BCRDV2 vaccinated group. DOI: http://dx.doi.org/10.3329/bjm.v28i2.11823 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 88-91